Mesoporous conductive ZnO / ZIF-8 composite material as well as preparation method and application thereof
By preparing mesoporous conductive ZnO/ZIF-8 composite materials, the problems of poor conductivity and unfavorable microporous structure of MOFs materials are solved, and high-performance gas sensing, photocatalysis and photoelectric detection effects are achieved.
Patent Information
- Application Number
- CN202411662653.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing MOFs materials have poor electrical conductivity and the microporous structure is not conducive to gas diffusion and reaction, which limits the improvement of their performance.
By combining ZnO with ZIF-8, using amphiphilic block copolymer as template agent, combined with surface partial oxidation technology, mesoporous conductive ZnO/ZIF-8 composite material was prepared.
The material has achieved high specific surface area, controllable pore size, high crystallinity, uniform crystallization and high carrier mobility, which significantly improves its performance in photocatalysis, photoelectric detection and gas sensing.
Smart Images

Figure CN119505342A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite material and a preparation method and application thereof, in particular to a mesoporous conductive ZnO / ZIF-8 composite material and a preparation method and application thereof. Background Art
[0002] With the further development of science and technology and economic society, the demand for high-performance sensors is increasing. Among them, gas sensors have shown strong prospects in health monitoring, Internet of Things, smart homes, smart city construction, etc., and have received close attention from a large number of scientific researchers. Mesoporous materials are widely used in gas sensing, adsorption separation, catalysis and other fields due to their advantages such as high porosity and high specific surface area. Metal-organic framework materials (MOFs) have broad application prospects in the fields of catalysis and sensing due to their highly ordered pore structure, ultra-high specific surface area, rigid structure with certain mechanical strength, chemical modifiability and many other advantages.
[0003] However, most MOFs materials have poor inherent conductivity, which greatly limits their application. On the other hand, MOFs materials are microporous structures with pore sizes below 2 nm, which is not conducive to the large-scale diffusion of external molecules (such as gases) participating in the reaction inside the MOFs material, thereby affecting the contact between the reaction molecules and more active sites inside the MOFs material, limiting the further improvement of the performance of MOFs materials.
[0004] ZIF-8 is a common low-conductivity MOFs material. Composite ZIF-8 with conductive materials is an effective method to improve the conductivity of ZIF-8. However, it has the disadvantages of phase separation, insufficient interface composite, and complex mass transfer paths caused by polycrystalline structure, which cannot effectively improve the conductivity and performance of MOFs. Summary of the invention
[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a mesoporous conductive ZnO / ZIF-8 composite material with easily available raw materials and simple operation. Another purpose of the present invention is to provide a mesoporous conductive ZnO / ZIF-8 composite material with high specific surface area, controllable pore size, high crystallinity, uniform crystallization, and high carrier mobility. Still another purpose of the present invention is to provide an application of a mesoporous conductive ZnO / ZIF-8 composite material in nitrogen dioxide gas sensors, photocatalysis, and photoelectric detection.
[0006] Technical solution: The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material of the present invention comprises the following steps:
[0007] Step 1, dissolving the amphiphilic block copolymer in an organic solvent and stirring evenly to obtain a solution A; dissolving 2-methylimidazole in deionized water and stirring evenly to obtain a homogeneous solution B; dissolving a zinc-containing metal salt in deionized water and stirring evenly to obtain a homogeneous solution C;
[0008] Step 2: Mix solution A and solution B, stir to obtain a homogeneous solution D, then mix solution C and solution D to obtain a homogeneous solution E, and continue stirring;
[0009] Step 3, centrifuging the stirred solution E, washing the product F with methanol, and stirring and soaking the product F in an organic solvent to obtain a product G;
[0010] Step 4: Partially oxidize the surface of product G in an air environment to obtain a mesoporous conductive ZnO-based composite material.
[0011] Furthermore, in step 1, the amphiphilic block copolymer is one or more of polystyrene-polyethylene oxide (PS-b-PEO), polyethylene oxide-polymethyl methacrylate (PEO-b-PMMA), polystyrene-poly 4-vinyl pyridine (PS-b-P4VP). The molecular weight of the hydrophilic segment of the amphiphilic block copolymer is 1000-9000 g / mol, and the molecular weight of the hydrophobic segment is 1000-40000 g / mol.
[0012] Furthermore, the organic solvent is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), dimethyl sulfoxide (DMSO), pyridine, and tetrahydrofuran (THF).
[0013] Furthermore, the zinc-containing metal salt is one or more of zinc nitrate, zinc chloride, zinc acetate and zinc sulfate.
[0014] Furthermore, the concentration ratio of the amphiphilic block copolymer, 2-methylimidazole, and zinc-containing metal salt is 0.5-20:1:0.2-5.
[0015] Furthermore, in step 2, the stirring speed is 20 to 600 rpm, and the stirring time is 6 to 12 hours.
[0016] Furthermore, in step three, the stirring and soaking temperature is 20 to 60° C., and the stirring and soaking time is 20 min to 24 h.
[0017] Furthermore, in step 4, the surface is partially oxidized by heating the temperature to 260-450° C. at a heating rate of 2-10° C. / min and keeping the temperature for 1-6 hours.
[0018] The mesoporous conductive ZnO / ZIF-8 composite material obtained by the preparation method of the mesoporous conductive ZnO / ZIF-8 composite material of the present invention is a rhombic dodecahedron with an average pore size of 10 to 50 nm.
[0019] The invention discloses an application of a mesoporous conductive ZnO / ZIF-8 composite material in nitrogen dioxide gas sensors, photocatalysis and photoelectric detection.
[0020] Preparation principle: Since it is very difficult to directly synthesize mesoporous ZIF-8 materials, the present invention uses an amphiphilic block copolymer as a template, a zinc salt as a zinc source, and 2-methylimidazole as an organic ligand. The hydrophobic segment of the amphiphilic block copolymer agglomerates in the solvent to form spherical micelles with the hydrophobic segment as the core and the hydrophilic segment as the shell. The organic ligand is adsorbed to the hydrophilic segment of the amphiphilic block copolymer through electrostatic attraction. After adding a zinc salt solution, zinc and the organic ligand grow around the micelle through coordination to form a ZIF-8 / template complex. The template is removed by stirring and soaking to obtain a mesoporous conductive ZnO / ZIF-8 composite material.
[0021] The surface partial oxidation process of mesoporous ZIF-8 in air environment can make the residual sp 2 The template agent of the hybrid carbon-carbon double bond generates an amorphous C skeleton to support the mesoporous structure in the oxidation process without being destroyed, and then removes the excess carbon after further oxidation to obtain a pure mesoporous conductive ZnO / ZIF-8 composite material. In the present invention, a new method is provided for preparing MOFs materials with both highly open structure and excellent conductivity, which expands the application range of MOFs materials.
[0022] Since the molecular weight of the block copolymer and the oxidation temperature have a great influence on the pore size and crystallinity of the mesoporous ZIF-8 material, respectively, the mesoporous ZIF-8 material obtained by using this method and adjusting the molecular weight of the block copolymer and the oxidation temperature appropriately has a pore size between 10 and 50 nm and has a high crystallinity. By changing the length of the hydrophobic segment and the hydrophilic segment of the amphiphilic block copolymer, mesoporous conductive ZnO / ZIF-8 composite materials with different pore sizes and specific surface areas can be synthesized. By controlling the length of the hydrophobic segment and the hydrophilic segment of the amphiphilic block copolymer, the ratio of zinc metal salt and organic ligand, ZIF-8 with different pore order and different sizes can be synthesized. By controlling the rotation speed, ZIF-8 with or without a mesoporous structure can be synthesized; by controlling the stirring and soaking temperature and time of the organic solvent, ZIF-8 with or without a mesoporous structure can be synthesized. By controlling the heating rate, oxidation temperature and holding time, mesoporous conductive ZnO / ZIF-8 composite materials with different compositions, structures and crystallinities can be synthesized. Beneficial effects: Compared with the prior art, the present invention has the following significant characteristics:
[0023] 1. The obtained mesoporous ZIF-8 material has the characteristics of high specific surface area, controllable pore size, high crystallinity, uniform crystallization and high carrier mobility, and has great application prospects in photocatalysis, photoelectric detection, gas sensing, etc.;
[0024] 2. It solves the conductivity problem of MOFs materials with poor conductivity and the problem of insufficient performance utilization caused by the inherent microporous structure of MOFs materials;
[0025] 3. The two-step method for synthesizing mesoporous conductive ZnO / ZIF-8 composite materials has readily available raw materials, simple preparation method, easy to repeat, and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is a SEM image of the mesoporous ZIF-8 material prepared in Example 1 of the present invention;
[0027] Figure 2 is a SEM image of the mesoporous conductive ZnO / ZIF-8 composite material prepared in Example 1 of the present invention;
[0028] Figure 3 is an XRD pattern of the mesoporous conductive ZnO / ZIF-8 composite material prepared in Example 1 of the present invention;
[0029] Figure 4 Graphs showing the NO2 gas sensing performance of different materials, wherein (a) is a response-recovery curve of the mesoporous conductive ZnO / ZIF-8 composite material obtained in Example 1 to 10 ppm NO2, (b) is a response-recovery curve of the non-mesoporous conductive ZIF-8 material obtained in Comparative Example 1 to 10 ppm NO2, (c) is a response-recovery curve of the mesoporous ZIF-8 material obtained in Comparative Example 2 to 10 ppm NO2, and (d) is a response graph of the mesoporous conductive ZnO / ZIF-8 composite material obtained in Example 1 to different types of gases;
[0030] Figure 5 This is the SEM image of the product obtained in Comparative Example 3;
[0031] Figure 6 This is the SEM image of the product obtained in Comparative Example 4;
[0032] Figure 7 This is the SEM picture of the product obtained in Comparative Example 6. DETAILED DESCRIPTION
[0033] The materials, reagents, instruments, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. Zinc nitrate, 2-methylimidazole, and tetrahydrofuran (THF) were purchased from Aladdin Reagents (Shanghai) Co., Ltd. Amphiphilic block copolymer polystyrene-polyethylene oxide (PS-b-PEO) was purchased from Aimejie Polymer Source.
[0034] Example 1
[0035] A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material comprises the following steps:
[0036] (1) Dissolve 10 mg of polystyrene-polyethylene oxide (PS-b-PEO) in 0.2 mL of tetrahydrofuran (THF) and stir to obtain a transparent solution A. The molecular weight of the hydrophilic segment of polystyrene-polyethylene oxide (PS-b-PEO) is 2150 g / mol, and the molecular weight of the hydrophobic segment is 6300 g / mol. Dissolve 19.7 mg of 2-methylimidazole in 2 mL of deionized water and stir to obtain a homogeneous solution B. Dissolve 100 mg of zinc nitrate in 2 mL of deionized water and stir to obtain a homogeneous solution C.
[0037] (2) Solution A and solution B were mixed and stirred at 500 rpm for 1 h to obtain a homogeneous solution D.
[0038] (3) While stirring, solution C was mixed with solution D to obtain a homogeneous solution E, and stirring was continued at the original speed for 12 h.
[0039] (4) The stirred solution E was centrifuged, and the product F (ZIF-8 / template composite material) was washed three times with methanol. The product F was stirred and immersed in tetrahydrofuran (THF) at 50°C for 1 h to obtain product G (mesoporous ZIF-8).
[0040] (5) The surface of product G is partially oxidized in an air environment, that is, the temperature is increased to 300°C at a heating rate of 5°C / min and kept at this temperature for 1 hour to obtain a mesoporous conductive ZnO-based composite material.
[0041] The mesoporous ZIF-8 material prepared in this example was analyzed by scanning electron microscopy. Figure 1 As shown. Figure 1 It can be seen that the ZIF-8 material prepared in this example has a rhombic dodecahedron structure, and the polyhedrons are distributed with a mesoporous structure, the pore size is uniform, and the average pore size is about 10 nm.
[0042] The mesoporous conductive ZnO / ZIF-8 composite material prepared in this example was analyzed by scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the mesoporous conductive ZnO / ZIF-8 composite material prepared in this example substantially completely retains the rhombic dodecahedron structure and mesoporous structure of the mesoporous ZIF-8 material, indicating that oxidation does not destroy the structure of the original mesoporous MOFs material.
[0043] The mesoporous conductive ZnO / ZIF-8 composite material prepared in this example was subjected to XRD analysis. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the mesoporous conductive ZnO / ZIF-8 composite material prepared in this example mainly shows the characteristic peak of ZIF-8, while the characteristic peak of ZnO is very weak, indicating that a mesoporous conductive ZnO / ZIF-8 composite material with a high degree of crystallinity is obtained.
[0044] Example 2
[0045] A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material comprises the following steps:
[0046] (1) Dissolve 10 mg of amphiphilic block copolymer polyethylene oxide-polymethyl methacrylate (PEO-b-PMMA) in 0.2 mL of N,N-dimethylformamide (DMF) and stir to obtain a transparent solution A. The molecular weight of the hydrophilic segment of polyethylene oxide-polymethyl methacrylate (PEO-b-PMMA) is 1000 g / mol, and the molecular weight of the hydrophobic segment is 1000 g / mol. Dissolve 19.7 mg of 2-methylimidazole in 0.5 mL of deionized water and stir to obtain a homogeneous solution B. Dissolve 10 mg of zinc chloride in 0.5 mL of deionized water and stir to obtain a homogeneous solution C.
[0047] (2) Solution A and solution B were mixed and stirred at 20 rpm for 1 h to obtain a homogeneous solution D.
[0048] (3) While stirring, solution C and solution D were mixed to obtain a homogeneous solution E, and stirring was continued at the original speed for 6 h.
[0049] (4) The stirred solution E was centrifuged, and the product F (ZIF-8 / template composite material) was washed three times with methanol. The product F was stirred and immersed in N,N-dimethylformamide (DMF) at 20°C for 20 min to obtain product G (mesoporous ZIF-8).
[0050] (5) The surface of product G was partially oxidized in an air environment, that is, the temperature was raised to 260°C at a heating rate of 2°C / min and kept at that temperature for 6 h to obtain a mesoporous conductive ZnO-based composite material with a pore size of about 10 nm.
[0051] Example 3
[0052] A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material comprises the following steps:
[0053] (1) 10 mg of amphiphilic block copolymer polystyrene-poly-4-vinylpyridine (PS-b-P4VP) was dissolved in 0.2 mL of dimethyl sulfoxide (DMSO) and stirred to obtain a transparent solution A. The molecular weight of the hydrophilic segment of polystyrene-poly-4-vinylpyridine (PS-b-P4VP) was 9000 g / mol, and the molecular weight of the hydrophobic segment was 40000 g / mol. 19.7 mg of 2-methylimidazole was dissolved in 5 mL of deionized water and stirred to obtain a homogeneous solution B. 150 mg of zinc acetate was dissolved in 5 mL of deionized water and stirred to obtain a homogeneous solution C.
[0054] (2) Solution A and solution B were mixed and stirred at 600 rpm for 1 h to obtain a homogeneous solution D.
[0055] (3) While stirring, solution C and solution D were mixed to obtain a homogeneous solution E, and stirring was continued at the original speed for 10 h.
[0056] (4) The stirred solution E was centrifuged, and the product F (ZIF-8 / template composite material) was washed three times with methanol. The product F was stirred and immersed in dimethyl sulfoxide (DMSO) at 60°C for 24 h to obtain product G (mesoporous ZIF-8).
[0057] (5) The surface of product G was partially oxidized in an air environment, that is, the temperature was raised to 450°C at a heating rate of 10°C / min and kept at that temperature for 2 h to obtain a mesoporous conductive ZnO-based composite material with a pore size of about 50 nm.
[0058] Example 4
[0059] A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material comprises the following steps:
[0060] (1) Dissolve 10 mg of amphiphilic block copolymer polystyrene-polyethylene oxide (PS-b-PEO) in 0.2 mL of pyridine and stir to obtain a transparent solution A. The molecular weight of the hydrophilic segment of polystyrene-polyethylene oxide (PS-b-PEO) is 5000 g / mol, and the molecular weight of the hydrophobic segment is 240000 g / mol. Dissolve 19.7 mg of 2-methylimidazole in 2 mL of deionized water and stir to obtain a homogeneous solution B. Dissolve 80 mg of zinc sulfate in 2 mL of deionized water and stir to obtain a homogeneous solution C.
[0061] (2) Solution A and solution B were mixed and stirred at 450 rpm for 1 h to obtain a homogeneous solution D.
[0062] (3) While stirring, solution C and solution D were mixed to obtain a homogeneous solution E, and stirring was continued at the original speed for 8 h.
[0063] (4) The stirred solution E was centrifuged, and the product F (ZIF-8 / template composite material) was washed three times with methanol. The product F was stirred and immersed in pyridine at 30°C for 12 h to obtain the product G (mesoporous ZIF-8).
[0064] (5) The surface of product G was partially oxidized in an air environment, that is, the temperature was raised to 300°C at a heating rate of 6°C / min and kept at that temperature for 4 hours to obtain a mesoporous conductive ZnO-based composite material with a pore size of about 30 nm.
[0065] Example 5
[0066] A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material comprises the following steps:
[0067] (1) Dissolve 10 mg of amphiphilic block copolymer polyethylene oxide-polymethyl methacrylate (PEO-b-PMMA) in 0.2 mL of N,N-dimethylacetamide (DMA) and stir to obtain a transparent solution A. The molecular weight of the hydrophilic segment of polyethylene oxide-polymethyl methacrylate (PEO-b-PMMA) is 3000 g / mol, and the molecular weight of the hydrophobic segment is 30000 g / mol. Dissolve 19.7 mg of 2-methylimidazole in 3 mL of deionized water and stir to obtain a homogeneous solution B. Dissolve 90 mg of zinc chloride in 3 mL of deionized water and stir to obtain a homogeneous solution C.
[0068] (2) Solution A and solution B were mixed and stirred at a stirring speed of 550 rpm for 1 h to obtain a homogeneous solution D.
[0069] (3) While stirring, solution C was mixed with solution D to obtain a homogeneous solution E, and stirring was continued at the original speed for 9 h.
[0070] (4) The stirred solution E was centrifuged, and the product F (ZIF-8 / template composite material) was washed three times with methanol. The product F was stirred and immersed in N,N-dimethylacetamide (DMA) at 40 °C for 6 h to obtain product G (mesoporous ZIF-8).
[0071] (5) The surface of product G was partially oxidized in an air environment, that is, the temperature was raised to 400°C at a heating rate of 8°C / min and kept at that temperature for 3 h to obtain a mesoporous conductive ZnO-based composite material with a pore size of about 20 nm.
[0072] Comparative Example 1
[0073] A method for preparing a non-mesoporous conductive ZIF-8 material comprises the following steps:
[0074] (1) Dissolve 2-methylimidazole in 2 mL of deionized water and stir to obtain a homogeneous solution A; dissolve zinc nitrate in 2 mL of deionized water and stir to obtain a homogeneous solution B.
[0075] (2) Solution A and Solution B were mixed to obtain Solution C, and the mixture was stirred for 12 h.
[0076] (3) The stirred solution C was centrifuged to obtain the non-mesoporous ZIF-8 material (D), and then the product D was washed three times with methanol.
[0077] (4) The surface of product D was partially oxidized in an air environment and kept at a certain temperature for 1 h to obtain a non-mesoporous conductive ZIF-8 material.
[0078] Comparative Example 2
[0079] A method for preparing a mesoporous ZIF-8 material comprises the following steps:
[0080] (1) The amphiphilic block copolymer polystyrene-polyethylene oxide (PS-b-PEO) was dissolved in 0.2 mL of tetrahydrofuran (THF) and stirred with a magnetic bar to obtain a transparent solution A; 2-methylimidazole was dissolved in 2 mL of deionized water and stirred to obtain a homogeneous solution B; zinc nitrate was dissolved in 2 mL of deionized water and stirred to obtain a homogeneous solution C.
[0081] (2) Solution A and Solution B were mixed and stirred for 1 h to obtain Solution D.
[0082] (3) While stirring, solution C and solution D were mixed to obtain solution E and the stirring was continued at the original speed for 12 h;
[0083] (4) The stirred solution E is centrifuged to obtain a ZIF-8 / template composite material (F), and then the product F is washed three times with methanol and stirred and immersed in tetrahydrofuran (THF) to obtain mesoporous ZIF-8.
[0084] Application comparison
[0085] The materials prepared in Example 1, Example 2 and Example 3 are respectively used to manufacture semiconductor gas sensors, and their comprehensive gas sensing performance is tested. Specifically, the gas sensing material is placed on a Pt electrode and placed in a 1.8L test chamber. The Xiaoyu Electronics M2.0 gas sensitive test instrument automatically records the real-time changes in the resistance of the gas sensing material. At the beginning of the test, a syringe is used to inject dry NO2 gas of several concentrations (2ppm, 4ppm, 6ppm, 8ppm, 10ppm), and the resistance begins to change. When the resistance stabilizes, the lid is opened, the gas sensing material contacts the air, and the resistance returns to the initial value. In this test, the sensitivity (responsivity) of the gas sensing material is defined as S=(R a -R g ) / R a , where R a and R g are the resistance values of the gas sensing material in air and test gas respectively. The results are as follows Figure 4 shown.
[0086] Figure 4 The figures are test graphs of the NO2 gas sensing performance of the materials prepared in Example 1, Comparative Example 1 and Comparative Example 2, wherein (a) is a response-recovery curve graph of the mesoporous conductive ZnO / ZIF-8 composite material obtained in Example 1 to 10ppm NO2, (b) is a response-recovery curve graph of the non-mesoporous conductive ZIF-8 material obtained in Comparative Example 1 to 10ppm NO2, (c) is a response-recovery curve graph of the mesoporous ZIF-8 material obtained in Comparative Example 2 to 10ppm NO2, and (d) is a response graph of the mesoporous conductive ZnO / ZIF-8 composite material obtained in Example 1 to different types of gases (nitrogen dioxide (10ppm), hydrogen (500ppm), methanol (50ppm), ethanol (50ppm), acetone (20ppm), formaldehyde (20ppm), ammonia (20ppm), benzene (20ppm), styrene (20ppm), hydrogen sulfide (20ppm)).
[0087] Depend on Figure 4 (a)–(c) It can be seen that compared with the non-mesoporous conductive ZIF-8 material and mesoporous ZIF-8 material prepared in Example 2 and Example 3, the mesoporous conductive ZnO / ZIF-8 composite material prepared in Example 1 has a better response to 10 ppm NO2. Although the mesoporous ZIF-8 has an increased specific surface area, it does not show a response to the gas due to its poor electrical conductivity. This shows that this method successfully improves the electrical properties of the ZIF-8 material, which is conducive to expanding its application range.
[0088] Depend on Figure 4(d) It can be seen that the sensitivity of the mesoporous conductive ZnO / ZIF-8 composite material sensor prepared in Example 1 to 10 ppm NO2 is much higher than that of other gases, especially methanol and ethanol, indicating that the sensor has extremely high selectivity for NO2.
[0089] Comparative Example 3
[0090] This comparative example aims to explore the effects of the length of the hydrophobic segment and the hydrophilic segment of the amphiphilic block copolymer and the ratio of the zinc-containing metal salt to the organic ligand on the pore order and size of the synthetic material.
[0091] The remaining steps of this comparative example are the same as those of Example 1, except that the molecular weight of the hydrophilic segment of polystyrene-polyethylene oxide (PS-b-PEO) is replaced with 500 g / mol and 10,000 g / mol, and the molecular weight of the hydrophobic segment is replaced with 500 g / mol and 50,000 g / mol, respectively. Figure 5 The results showed that when the molecular weight of the block copolymer was too small, ZIF-8 had no obvious mesoporous structure; when the molecular weight of the block copolymer was too large, disordered pores or even no pores were generated on the surface of ZIF-8.
[0092] Comparative Example 4
[0093] This comparative example aims to explore the effect of stirring speed on the pore structure of the synthetic material.
[0094] The remaining steps of this comparative example are the same as those of Example 1, except that the stirring speed is replaced with 300 rpm and 700 rpm respectively. Figure 6 The results showed that: on the one hand, low rotation speed can make MOFs grow uniformly, and on the other hand, it can also ensure the interaction between the template and the MOFs precursor, so that ZIF-8 can grow along the periphery of the template, thus forming a mesoporous structure; when the rotation speed is high, the template and the MOFs precursor cannot effectively interact with each other, resulting in phase separation of MOFs and the template, and thus ZIF-8 with a mesoporous morphology cannot be synthesized.
[0095] Comparative Example 5
[0096] This comparative example aims to explore the effects of stirring immersion temperature and time on the pore structure of the synthetic material.
[0097] The remaining steps of this comparative example are the same as those of Example 1, except that the stirring and soaking in step (4) is replaced by stirring and soaking at 70°C for 10 min and stirring and soaking at 10°C for 30 h. SEM characterization was performed, and it was found that when the soaking temperature and soaking time were short, the template in the ZIF-8 mesopores could not be effectively removed, resulting in an unclear mesoporous structure; when the soaking temperature and soaking time were too long, the mesoporous structure would be destroyed under the action of solvent molecules.
[0098] Comparative Example 6
[0099] This comparative example aims to explore the effects of heating rate, oxidation temperature and holding time on the pore structure of the synthetic material.
[0100] The remaining steps of this comparative example are the same as those of Example 1, except that step (5) is replaced by ① heating to 500°C at a heating rate of 1°C / min and keeping warm for 0.5h; ② heating to 200°C at a heating rate of 12°C / min and keeping warm for 8h. Figure 7 The results showed that: when the temperature is too high or the insulation time is too long, ZIF-8 will be completely oxidized to ZnO, the original structure will be destroyed under the action of high temperature, and agglomeration will occur; when the insulation time is too short, no sufficient ZnO conductive layer can be produced on the surface of ZIF-8, thereby failing to effectively improve the conductivity of ZIF-8.
Claims
1. A method for preparing a mesoporous conductive ZnO / ZIF-8 composite material, characterized in that: The following steps are involved: Step 1, dissolving the amphiphilic block copolymer in an organic solvent and stirring to obtain a solution A; Dissolve 2-methylimidazole in deionized water, stir evenly to obtain a homogeneous solution B; dissolve a zinc-containing metal salt in deionized water, stir evenly to obtain a homogeneous solution C; Step 2: Mix solution A and solution B, stir to obtain a homogeneous solution D, then mix solution C and solution D to obtain a homogeneous solution E, and continue stirring; Step 3, centrifuging the stirred solution E, washing the product F with methanol, and stirring and soaking the product F in an organic solvent to obtain a product G; Step 4: Partially oxidize the surface of product G in an air environment to obtain a mesoporous conductive ZnO-based composite material.
2. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 1, the amphiphilic block copolymer is one or more of polystyrene-polyethylene oxide, polyethylene oxide-polymethyl methacrylate, and polystyrene-poly 4-vinyl pyridine; the molecular weight of the hydrophilic segment of the amphiphilic block copolymer is 1000-9000 g / mol, and the molecular weight of the hydrophobic segment is 1000-40000 g / mol.
3. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, pyridine and tetrahydrofuran.
4. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 1, the zinc-containing metal salt is one or more of zinc nitrate, zinc chloride, zinc acetate and zinc sulfate.
5. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 1, the concentration ratio of the amphiphilic block copolymer, 2-methylimidazole, and zinc-containing metal salt is 0.5-20:1:0.2-5.
6. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 2, the stirring speed is 20 to 600 rpm, and the stirring time is 1 to 12 hours.
7. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 3, the stirring and soaking temperature is 20 to 60° C., and the stirring and soaking time is 20 min to 24 h.
8. The method for preparing a mesoporous conductive ZnO / ZIF-8 composite material according to claim 1, characterized in that: In the step 4, the surface is partially oxidized by heating the temperature to 260-450° C. at a heating rate of 2-10° C. / min and keeping the temperature for 1-6 hours.
9. The mesoporous conductive ZnO / ZIF-8 composite material obtained by the preparation method of the mesoporous conductive ZnO / ZIF-8 composite material according to any one of claims 1 to 8, characterized in that: The mesoporous conductive ZnO / ZIF-8 composite material is a rhombic dodecahedron with an average pore diameter of 10 to 50 nm.
10. Use of the mesoporous conductive ZnO / ZIF-8 composite material according to claim 9 in nitrogen dioxide gas sensors, photocatalysis, and photoelectric detection.
Citation Information
Patent Citations
Carbon-based catalyst with hierarchical pore structure as well as preparation method and application of carbon-based catalyst
CN113451592A
Synthetic method for in-situ construction of defective ZIF-8 / ZnO ordered macroporous heterostructure material
CN115945219A
Ordered bicontinuous structure metal organic framework material SP-ZIF-8 as well as preparation method and application thereof
CN116120580A
Ordered macroporous metal-organic framework single crystals and preparation method thereof
US20210213436A1